OPTIMALISAI MANAJEMEN PEMBINAAN KEROHANIAN WBP DILAPAS KLAS IIB GUNUNGSITOLI MELALUI IMPLEMENTASI SISTEM SIMOPENA (SISTEM MONITORING PEMBINAAN NARAPIDANA) SISTEM KONTROL MENGIKUTI KEGIATAN KEAGAMAAN DI LAPAS KELAS II B GUNUNGSITOLI - Afolo Mendrofa; Maria Magdalena Bate'e; Natal Fisman Zebua; Serniati Zebua (Jurnal Publikasi Manajemen Informatika, 2026)
The phenomenon underlying this research is the limited effectiveness of spiritual guidance programs for inmates at the Class IIB Penitentiary (Lapas) of Gunungsitoli, which function not only as a means of religious development but also as a medium for social reintegration. The main problem addressed in this study is how the control system and the implementation of spiritual guidance programs are carried out, as well as the extent to which these programs are able to enhance inmates’ religious awareness, moral values, and social behavior. This research employed a descriptive qualitative approach using interviews, observation, and documentation to collect data from correctional officers, religious leaders, and inmates. The findings indicate that the implementation of spiritual guidance in Lapas Class IIB Gunungsitoli has been conducted in line with established procedures; however, its effectiveness is still influenced by limited facilities, the level of officer involvement, and the participation rate of inmates. The control system applied through regular evaluations and spiritual mentoring has proven helpful in fostering discipline and increasing religious awareness among most inmates. Thus, spiritual guidance plays a significant role in the correctional process, although improvements are still required in terms of facilitator quality, the provision of adequate worship facilities, and the strengthening of control systems to achieve optimal outcomes.